2016
DOI: 10.7150/jca.16798
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of RNF128 Predicts Progression and Poor Prognosis in Patients with Urothelial Carcinoma of the Upper Tract and Urinary Bladder

Abstract: Background: The TP53 tumor suppressor gene plays a crucial role in the carcinogenesis of many malignancies, including urothelial carcinoma (UC). Overexpression of p53 is associated with poor prognosis in UC. Recently, RING finger protein 128 (RNF128) was shown to be involved in p53-induced apoptosis, forming a negative feedback loop. However, the significance of RNF128 in patients with UC remains unknown. In this study, our aim was to evaluate the expression of RNF128 in UC and to assess its predictive and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…Chen et al found that RNF128, as a tumor promoter, physically interacts with and degrades p53 under stress conditions [27]. Conversely, Lee et al found that downregulation of RNF128 was associated with the reduced survival in patients with urothelial carcinoma [28]. Here, we found that RNF128 expression is downregulated in melanoma compared with that in adjacent peritumoral tissues.…”
Section: Discussionmentioning
confidence: 43%
“…Chen et al found that RNF128, as a tumor promoter, physically interacts with and degrades p53 under stress conditions [27]. Conversely, Lee et al found that downregulation of RNF128 was associated with the reduced survival in patients with urothelial carcinoma [28]. Here, we found that RNF128 expression is downregulated in melanoma compared with that in adjacent peritumoral tissues.…”
Section: Discussionmentioning
confidence: 43%
“…19 In addition, RNF128 also regulates energy metabolism 20 and cytoskeletal reorganization. 21 RNF128 has recently been documented to be involved in the progression of diverse cancers, including esophageal cancer, 12 melanoma, 13 urothelial carcinoma 14 and lymphoma. 11 Nonetheless, the role of RNF128 in HCC remains unexplored.…”
Section: Dovepressmentioning
confidence: 99%
“…12 In melanoma, however, RNF128 regulates Wnt/β-catenin signaling to suppress EMT and stemness through a mechanism involving CD44 ubiquitination. 13 RNF128 downregulation is associated with poor prognosis in upper urinary tract and bladder cancer, 14 whereas there is a lack of research about the role of RNF128 in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The corollary to this is the impact on SATB2 targeted loci during differentiation, where SATB2 is removed from the nucleus, which simultaneously represses growth-related euchromatic genes and relieves repression of differentiation-specific genes that were previously sequestered in the heterochomatic regions of the nucleus. This hypothesis is supported by the ChIP-and RNA-seq data where a number of genes that are potent promoters of cell proliferation were downregulated during early myoblast differentiation, including Hdac9 (Lapierre et al 2016), Celf1 (Xia et al, 2015), Ncoa1 (Wang et al, 2018), Hdgfrp3 (Xiao et al, 2013), and Rnf128 (Lee et al, 2016), all of which were significantly downregulated following SATB2 removal during early stages of the differentiation program ( Figure 3F).…”
Section: Discussionmentioning
confidence: 68%